2018
DOI: 10.1021/acs.analchem.8b02068
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Response Fluorescent Probe for the Detection of Viscosity and H2S and Its Application in Studying Their Cross-Talk Influence in Mitochondria

Abstract: Intracellular viscosity is an essential microenvironmental parameter and HS is a critical gaseous signaling molecule, which are both related to various physiological processes. It is reported that the change of viscosity and an imbalance of HS production in the mitochondria are both associated with overexpression of amyloid betapeptide (Aβ), which is thought to play a central role in the pathogenesis of Alzheimer's disease (AD). However, to our best knowledge, no fluorescent probe is found for dual detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(78 citation statements)
references
References 50 publications
1
75
0
1
Order By: Relevance
“…This enhancement might origin from the mitochondria shrinkage to increase local viscosity in mitochondrial membrane. To exclude the effect of mitochondria membrane potential (MMP), we co-stained the mitochondria with Coupa and a MMP-independent mitochondria probe, mitochondria-GFP 25 , and imaging with or without CCCPaltering MMP demonstrated that Coupa labeling mitochondria is not dependent on MMP, similar to that of mitochondria-GFP ( Supplementary Fig. 9), and CCCP-treatment made the blue fluorescence increase with that of the MMP-independent probe GFP ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhancement might origin from the mitochondria shrinkage to increase local viscosity in mitochondrial membrane. To exclude the effect of mitochondria membrane potential (MMP), we co-stained the mitochondria with Coupa and a MMP-independent mitochondria probe, mitochondria-GFP 25 , and imaging with or without CCCPaltering MMP demonstrated that Coupa labeling mitochondria is not dependent on MMP, similar to that of mitochondria-GFP ( Supplementary Fig. 9), and CCCP-treatment made the blue fluorescence increase with that of the MMP-independent probe GFP ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although conventional dyes (e.g., mitochondria-tracker and lysosometracker probes) report the morphology of mitochondria and lysosomes 3 , they are insensitive to viscosity and therefore do not track the dynamic changes of an organelle's internal environment. Recently developed viscosity probes 22 can realize the imaging of the viscosity of a single organelle by using fluorescent probe with rotatable C sp 2 -C sp 2 bond [23][24][25] . In Coupa, there is also C 2p 2 -C sp 2 bond in its molecule skeleton, this may provide Coupa also the fluorescent viscosity sensing ability.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S3 in the Supporting Information, this timedependent process gave the k obs of 0.0255 min À 1 under pseudo-first-order conditions, which is similar with the reported values of most H 2 S recognized probes. [31][32][33] There wasn't dramatic attenuation for the fluorescence intensities in the subsequent measurement after it reached a saturation at 40 min, indicating the high photostability of the ZAIS-Cu probe. Figure S4 in the Supporting Information shows the effect of pH on fluorescence response of ZAIS-Cu-6 to H 2 S. The fluorescence intensity displayed the maximal enhancement at the pH range of 5.0-7.0 upon the addition of NaHS (50 μM), implying the good applicability of this probe under the physiological condition.…”
Section: Resultsmentioning
confidence: 97%
“…D) Reproduced with permission. [ 165 ] Copyright 2018, American Chemical Society. E) Representation of probe 127 (Mito‐NIRHV) detecting viscosity and H 2 O 2 in an AD brain model.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…HeLa cells were pretreated with probe 126 followed by Na 2 S that resulted in intense green fluorescence. [ 165 ] There is a possibility that the probe could be part of the mitochondria‐targeted therapeutic interventions and may slow down the AD progression.…”
Section: Alzheimer's Diseasementioning
confidence: 99%